OP0083 Molecular targeted imaging biomarkers for personalized medicine strategies in systemic sclerosis-related interstitial lung disease. (15th June 2017) - Schniering, J; Benešová, M; Brunner, M; Feghali-Bostwick, C; Schibli, R; Distler, O; Müller, C; Maurer, B
Abstract : Background: Interstitial lung disease (ILD) is a life-threatening complication in systemic sclerosis (SSc). Substantial research progress has identified distinct genomic and molecular subtypes in SSc-ILD and brought molecular targeted therapies within reach. However, personalized medicine approaches are still lacking since clinically applicable tools for individualized patient stratification are not yet available. Objectives: To assess the possibility of imaging molecular targets as a biomarker for stage-dependent assessment of ILD in the mouse model of bleomycin-induced lung fibrosis. Methods: Expression of integrin αv β3 and folate receptor β (FR-β) was analyzed in lung tissues from patients with idiopathic pulmonary fibrosis (IPF), SSc-ILD, and healthy controls as well as from bleomycin treated mice and saline treated controls using immunohistochemistry and qPCR (n=5–11). SPECT (Single Photon Emission Computed Tomography) or PET (Positron Emission Tomography) was performed at days 3, 7, and 14 after bleomycin instillation using the integrin αv β3 -specific 177 Lu-c(RGDfK)-ligand and the FR-β-specific 18 F-Azafol. Additionally, 18 F-FDG-PET and high resolution CT (HRCT) scans were performed. The specific lung uptake of the radiotracers over time was assessed by ex vivo SPECT or PET/CT scans and biodistribution studies. Results: Expression of FR-β was significantly increased at the mRNA and protein level of SSc-ILD patients as compared to healthy subjects (p<0.05), whereas only its gene expression was upregulated in IPF patients (p<0.01). Integrin αv β3 was increased at the protein level of both SSc-ILD and IPF patients (p<0.05), while its mRNA expression was not significantly altered. Similarly, in lungs of bleomycin treated mice, but not of controls, FR-β expression was increased time-dependently at the mRNA and protein level with higher expression at day 3 and day 7, the inflammatory stages of bleomycin-induced lung fibrosis (p<0.05). In contrast, expression of integrin αv β3 was upregulated at day 7 and day 14 at the protein, but not at the mRNA level in bleomycin treated mice, and thus not only in the inflammatory but also in the fibrotic stages (p<0.05). 18 F-FDG-PET and HRCT detected time-dependent changes of metabolic activity and ILD morphology in bleomycin treated mice. However, compared with these routinely employed unselective imaging techniques, molecular targeted imaging of integrin αv β3 and FR-β successfully visualized ILD and discriminated lung inflammation and/or fibrosis in a time-dependent manner and in correspondence with the expression changes at the tissue level. The specific lung uptake of 177 Lu-c(RGDfK)-ligand and 18 F-Azafol as compared with the unspecific uptake of 18 F-FDG in diseased lungs over time was demonstrated by biodistribution studies and ex vivo SPECT or PET/CT scans. Conclusions: Our data suggest that stage-dependent visualization of ILD with radiotracers that target key markers of lung inflammation and/or fibrosis shows promise for clinical application. As opposed to unselective imaging techniques such as 18 F-FDG-PET and HRCT, the introduction of specific imaging biomarkers for individualized management of SSc-ILD patients could represent the first step towards precision medicine. Disclosure of Interest: J. Schniering Grant/research support from: Swiss National Science Foundation (S-85605–02–01), M. Benešová Grant/research support from: Swiss National Science Foundation (S-85605–02–01), M. Brunner: None declared, C. Feghali-Bostwick: None declared, R. Schibli Grant/research support from: Merck & Cie, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi; Patent licensed: mir-29 for the treatment of systemic sclerosis, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha, C. Müller Grant/research support from: Merck & Cie, B. Maurer Grant/research support from: AbbVie, Protagen, EMDO, Novartis, Pfizer, Roche, Actelion; Patent licensed: mir-29 for the treatment of systemic sclerosis